Success through diversity : why the most inclusive companies will win - Fulp, Carol, 1952-; Patrick, Deval (Boston : Beacon Press, 2018)
'Explores how investing in a racially and ethnically diverse workforce will help make contemporary businesses more dynamic, powerful, and profitable In our fast-changing demographic landscape, companies that proactively embrace diversity in all areas of their operations will be best poised to thrive. Renowned business leader and visionary Carol Fulp explores staffing trends in the US and provides a blueprint for what businesses must do to maintain their competitiveness and customer base, including hiring in new ways, aligning managers around diversity, providing new kinds of leadership development, and engaging employees to embrace differences. Using detailed case histories of corporate cultures such as the NFL, Eastern Bank, John Hancock, Hallmark Health, and PepsiCo, as well as her own experiences in the workplace and in advising companies on diversity practice, Fulp demonstrates how people of different races and ethnicities represent an essential asset to contemporary companies and organizations'--
'Demographic shifts in America have made diversity one of the most important topics in contemporary business. Companies that proactively embrace diversity in all areas of their operations will thrive, while companies that ignore this shift will find it impossible to maintain relevance and compete'--
'Foreword by Deval Patrick.'--Dust jacket.
Includes bibliographical references and index.
Keywords: Diversity in the workplace; Strategic planning; Leadership